The isochoric thermal conductivity of solid n-alkanes: propane C₃H₈ - Konstantinov, V.A.; Revyakin, V.P.; Sagan, V.V. (Физика низких температур, 2009)
The isochoric thermal conductivity of solid propane C₃H₈ has been investigated on three samples of different
densities in the temperature interval from 50 K to the onset of melting. In all the cases the isochoric thermal
conductivity exhibits dependences that are weaker than Λα1/T. The results obtained are compared with those
for other representatives of n-alkanes. The experimental data are discussed within a model in which the heat is
transported by low-frequency phonons and by «diffusive» modes above the phonon mobility edge.